The collection of Lidia Falcón: an archive for the history of the feminist movement since the 1960s - Jareño Gila, Claudia (Investigaciones Feministas (Feminist Research), 2019)
One of the greatest challenges in the history of struggles for women’s rights is the collection and conservation of documents generated by associations, collectives and individuals that were part of the Feminist Movement during the Spanish Transition to democracy. With the aim of highlighting part of their content, this article presents the Lidia Falcón Fonds as well as the Feminist Party and the Feminist Vindication Club Fonds, available for consultation at the National Archive of Catalonia. The fonds consist of all the documents produced in many projects led by Falcón –a lawyer, writer, journalist but also a dramatist and untiring feminist militant– among which we may underline the publication of two magazines –Vindicación Feminista y Poder y Libertad– as well as the foundation of the Feminist Party of Spain. Therefore, the diversity and volume of documents collected make these two fonds essential for the study and reconstruction of the history of this movement.